Caspase-8 regulation of TRAIL-mediated cell death - Crowder, R.N.; El-Deiry, W.S. (Experimental Oncology, 2012)
Research on TNF-related apoptosis-inducing ligand (TRAIL) and TRAIL receptors has advanced tremendously over the past 17 years. Initial observations of TRAIL and TRAIL receptor-mediated tumor cell toxicity led to enthusiasm of exploiting this selective, malignant cell killing for cancer therapy. Further examination revealed aberrant TRAIL signaling in some cancer cells leading to protection from TRAIL-mediated cell death. Mechanisms of TRAIL resistance often involve decreased expression or activity of initiator caspase-8, crucial for complete TRAIL signal transduction. Caspase-8 mutations, epigenetic silencing, decrease in stability, and incomplete activation have been reported. This article reviews the discovery of TRAIL and TRAIL receptors and subsequent studies that reveal how expression and function of caspase-8 are central to TRAIL-mediated cell death. This article is part of a Special Issue entitled “Apoptosis: Four Decades Later”.